Late‐life rapamycin treatment reverses age‐related heart dysfunction. Issue 5 (7th July 2013) - Flynn, James M.; O'Leary, Monique N.; Zambataro, Christopher A.; Academia, Emmeline C.; Presley, Michael P.; Garrett, Brittany J.; Zykovich, Artem; Mooney, Sean D.; Strong, Randy; Rosen, Clifford J.; Kapahi, Pankaj; Nelson, Michael D.; et al.
Summary: Rapamycin has been shown to extend lifespan in numerous model organisms including mice, with the most dramatic longevity effects reported in females. However, little is known about the functional ramifications of this longevity‐enhancing paradigm in mammalian tissues. We treated 24‐month‐old female C57BL/6J mice with rapamycin for 3 months and determined health outcomes via a variety of noninvasive measures of cardiovascular, skeletal, and metabolic health for individual mice. We determined that while rapamycin has mild transient metabolic effects, there are significant benefits to late‐life cardiovascular function with a reversal or attenuation of age‐related changes in the heart. RNA‐seq analysis of cardiac tissue after treatment indicated inflammatory, metabolic, and antihypertrophic expression changes in cardiac tissue as potential mechanisms mediating the functional improvement. Rapamycin treatment also resulted in beneficial behavioral, skeletal, and motor changes in these mice compared with those fed a control diet. From these findings, we propose that late‐life rapamycin therapy not only extends the lifespan of mammals, but also confers functional benefits to a number of tissues and mechanistically implicates an improvement in contractile function and antihypertrophic signaling in the aged heart with a reduction in age‐related inflammation.